Synthesis and Solvatochromic Behavior of Zwitterionic Donor–Bridge–Acceptor Systems with Oligo(p-phenylene) Spacers - Irina Zharinova (Organic Materials, 2021)
Abstract Oligo(p-phenylene)s with a donor phenol group and an acceptor pyridinium moiety separated by one and two p-phenylene units were synthesized by the linear iterative Suzuki–Miyaura coupling method using aryl nonaflates as effective coupling reagents. Zwitterionic forms of these push–pull molecules were generated upon deprotonation of the phenol leading to large redshifts in absorbance maxima. UV-vis absorbance studies also revealed strong dependence of the band position on solvent polarity: a smooth bathochromic shift can be observed with the decrease of the solvent polarity. The molecule with one p-phenylene bridging unit showed the strongest solvatochromic characteristics in the series, spanning the range of 167 nm while moving from polar water to less polar N,N-dimethylformamide. The magnitude of this shift was close to Reichardt's dye — one of the most solvatochromic organic dyes known.